Role of physical fragmentation and invertebrate activity in the breakdown rate of leaves - Ferreira, Verónica (2006)
We evaluated the relative importance of current velocity and invertebrate activities in the breakdown rate of alder [Alnus glutinosa (L.) Gaertner] leaves. Decomposition experiments were carried out in artificial channels, where current velocity and shredder presence were manipulated, and in a 4th order stream, in both summer and autumn, where litter bags were incubated in several reaches differing in both depth and current velocity. Alder leaves incubated in artificial channels decomposed significantly faster in the presence of shredders than in their absence (k = 0.0368/d vs. k = 0.0210/d in low current and k = 0.0472/d vs. k = 0.0219/d in high current). However, current (up to 2.35 m/s) had no significant effect on decomposition rates. In channels without invertebrates, no significant differences in k values were found between coarse and fine mesh bags in high (0.20 m/s) and low (0.05 m/s) current. Leaves incubated in the stream during summer, in reaches with current velocity ranging from 0.003 to 1.185m/s, did not differ in their decomposition rates (k = 0.0489/d to k = 0.0645/d). In autumn, leaves exposed to high current (1.228 m/s) had faster decomposition rate (k = 0.0417/d vs. k = 0.0136/d), which may be related to sediment transport during this time of the year or to the tendency for higher number of shredders in high current-shallow reaches.